The Role of Privatization on the Development of Sport Tourism in Guilan Province - Siavash Khodaparast; Bisotoon Azizi; Vahid Bakhshalipour; Nasrin Touba (Universidad de Antioquia, 2020)
Introduction: The purpose of this study was to investigate the role of privatization on the development of sport tourism in Guilan province. Materials and Methods: The research method was descriptive-survey based on structural equation model. The statistical population of this study was included managers of sport teams, sports management professors, managers of tourism agencies, and agency staff that 140 subjects were randomly selected as the sample. Questionnaires were distributed among the sample members after the confirmation of the validity of the questionnaires. Research hypotheses were analyzed by t-test and structural equation modeling by SPSS and LISREL software. Results: The results showed the privatization of sport tourism led to the development of seven identified components.